Analysis of Compensatory Corneal Epithelial Thickness Changes in Keratoconus Using Corneal Tomography. Issue 3 (March 2020) - Franco, Jimena; White, Craig A.; Kruh, Jonathan N.
Abstract : Purpose: To determine patterns of epithelial remodeling in keratoconus and to assess changes in these patterns as the disease progresses. Methods: This is a prospective case series. Patients with keratoconus undergoing corneal collagen crosslinking underwent Scheimpflug imaging before and after epithelial debridement. Analysis was performed to determine maps of epithelial thickness and change in keratometry. Maps were analyzed for patterns, and map SD was quantified. Measures were compared across the patients as grouped by the severity of disease. Results: The study comprised 38 eyes from 30 patients. Patients were stratified using the Amsler–Krumeich classification of keratoconus severity, with 17, 14, and 7 patients in the stage I, stage II, and stage III groups, respectively. A pattern of central epithelial thinning (to approximately 20 μm) with an annulus of epithelial thickening (to approximately 30–40 μm) was demonstrated. Changes were more pronounced in the later stages of the disease, with the average central thickness decreasing from 23 μm in stage I to 18 μm in stage III. Central corneal steepening of 1.5 to 1.9 diopters and peripheral flattening of 1.4 to 2.0 diopters after epithelial debridement were demonstrated. Analysis of map SD revealed a significant difference between stage III patients and patients at earlier stages of disease. Conclusions: The "doughnut pattern" of epithelial remodeling in keratoconus is supported by Scheimpflug imaging. This pattern is demonstrated to partially compensate for central corneal steepening seen in keratoconus.